Automatic Detection System Satellite Orbit Position with a Method of Control Azimuth and Elevation Angles Parabolic Antenna - Budi Herdiana; Deddy Gunawan (Universitas Muhammadiyah Yogyakarta, 2021)
The automatic system satellite signal strength tracking model through the positioning of the receiving antenna is one way to reduce the problem of attenuation and signal strength instability which is quite influential in tracking the satellite orbit position. The method of applying the antenna movement technique by adjusting the azimuth and elevation angles is possible to detect the position of the satellite orbit trajectory accurately. Therefore, the expected goal is to know the existence of the satellite's orbital trajectory and ensure that the signal strength it transmits will always be stable in all conditions. The empirical quantitative method is used to support the achievement of these objectives where the technique is carried out through field observations and device design involving calculations and applied mathematical equations based on information on satellite position data as a tracking object as well as a source of signal strength. Based on the test results, it shows that all the positions of the tracked satellite orbital trajectories produce a minimum and maximum azimuth-elevation angle of 0.52% - 4.02% and 0.25% - 3.99% when the system detects NSS6. Furthermore, when the system detects Palapa D, the minimum values for the percentage of maximum deviation error are 0.6% and 4.67% with a tolerance of the alignment angle to the satellite of 20. Overall, the designed system is able to track the position of the satellite's orbit path based on the level of signal strength stability on the parabolic receiver antenna which is designed with a small percentage of angle error.